Research status and development trend of solid food filling technology and equipment - LI Zhenlong; ZHANG Ke; DU Zhilong; ZHANG Lina; JIAN Huabin (Shipin yu jixie)
The filling of solid food is a key technical problem to be solved in the process of solid food packaging. It has significant advantages in ensuring the uniformity of solid food products and improving food quality. This paper reviews the research status of solid food filling technology and equipment, including the material characteristics and filling requirements of solid food, the classification of filling technology, the main principle and structure of filling equipment, etc., and analyzes the development trend of solid food filling technology and equipment. The research direction is proposed to provide theoretical basis and technical support for the development of solid food filling technology and the popularization and application of equipment.